1991
DOI: 10.1007/bf01319227
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity among bovine herpesvirus 4 field isolates

Abstract: Twenty-eight Belgian field isolates of bovine herpesvirus 4 (BHV-4) coming from a variety of clinical diseases have been studied by restriction analysis and Southern blot hybridization. The unique central part of the genome was very well conserved among strains; only one variation in a restriction site was detected in 3 isolates which contain an additional EcoRI site also present in the LVR 140 strain; three regions in the unique part of the genome varied in size, one of these was highly variable. The polyrepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0
4

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
3
13
0
4
Order By: Relevance
“…Direct nucleotide sequence repeats were found in the B and E regions. These regions, without ORFs, have been shown to vary in size between BHV-4 isolates (Bublot et al, , 1991. A variable number of repeats is probably responsible for this size variation as is the case with many other herpesviruses Kinoshita et al, 1988;Simon et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct nucleotide sequence repeats were found in the B and E regions. These regions, without ORFs, have been shown to vary in size between BHV-4 isolates (Bublot et al, , 1991. A variable number of repeats is probably responsible for this size variation as is the case with many other herpesviruses Kinoshita et al, 1988;Simon et al, 1989).…”
mentioning
confidence: 99%
“…The BHV-4 virion contains a dsDNA of 144_+6 kb (Ehlers et al, 1985). Molecular data have shown a clear relationship between BHV-4 and the members of the subfamily gammaherpesvirinae (Honess, 1984;Bublot et al, 1990Bublot et al, , 1991Bublot et al, , 1992van Santen, 1991 ;Thiry et al, 1992). Therefore, the Herpesvirus Study Group of the International Committee on Taxonomy of Viruses recently assigned BHV-4 to this subfamily (Roizman et al, 1992).…”
mentioning
confidence: 99%
“…The two additional BamHI sites present at the left end of HVA-2 L-DNA and the size variation of the corresponding BHV-4 (V. Test) BamHI fragment K have not previously been reported; all the other size variations detected in this study (HindlII fragment Q, BamHI fragment I, Jl and the prDNA fragment) have been observed in DNA from different BHV-4 strains (Ehlers et al, 1985;Bublot et al, 1990Bublot et al, , 1991. Furthermore, the presence of a variable amount of prDNA of one size in different DNA preparations, also observed for HVA-2 by Fuchs et al (1985), has been described for BHV-4 .…”
Section: Short Communication 717 (A)mentioning
confidence: 64%
“…The size variation present at the left end of L-DNA could be localized to HindIII fragment Q (positions 0.063 to 0.082) (Fig. 1 a and 3); HindIII fragment U, which is known to vary in size between BHV-4 strains (Bublot et aL, , 1991, was the same size in the two strains analysed in this study (Fig. 1 a).…”
Section: Short Communication 717 (A)mentioning
confidence: 67%
“…The unique central part of the genome is very well conserved among strains with a few variations due to the presence or absence of a restriction site and fragment length variation. A study of genomic diversity of field isolates in Belgium revealed some Movar-like isolates carrying an additional EcoRI site (Bublot et al, 1991b). The length variations occurred in the junction regions between repeated and unique sequences and two regions V1, V2 where the left junction and V1 regions are highly polymorphic (Bublot et al, , 1991a.…”
mentioning
confidence: 99%